Prevalence of Antibodies to Zika Virus in Mothers from Hawaii Who Delivered Babies with and without Microcephaly between 2009-2012. - Mukesh Kumar; Lauren Ching; Joshua Astern; Eunjung Lim; Alexander J Stokes; Marian Melish; Vivek R Nerurkar (Public Library of Science (PLoS), 2016)
Zika virus (ZIKV) is an emerging mosquito-borne pathogen. ZIKV infection is linked to the development of severe fetal abnormalities that include spontaneous abortion, stillbirth, hydranencephaly, and microcephaly. ZIKV outbreaks have been recorded in the United States. We recently demonstrated the first congenital ZIKV infection in the United States. In this study, we investigated archived blood samples from six mothers who gave birth to babies with microcephaly and 12 mothers who gave birth to healthy babies in Hawaii between 2009 and 2012. We tested maternal blood for the presence of ZIKV IgM and IgG antibodies using commercially available human ZIKV IgM and IgG ELISA kits. Blood from one mother who delivered babies with microcephaly tested positive for ZIKV IgM antibody (16.6%) and blood from three mothers tested positive for ZIKV IgG antibody (50%). ZIKV showed a trend toward significance with microcephaly. ZIKV IgG antibody positive mothers were more likely to deliver babies with microcephaly than mothers who were negative for ZIKV IgG antibodies (Odds ratio [OR] = 11.0, 95% confidence interval [CI] = 0.8-147.9, p = 0.083). Similarly, ZIKV IgM antibody positive mothers were also more likely to deliver babies with microcephaly than mothers who were negative for ZIKV IgM antibody (OR = 6.8, 95% CI = 0.2-195.1). These data provide further evidence of a link between ZIKV infection and microcephaly and suggests presence of ZIKV positive cases and associated microcephaly in the United States as early as 2009.